INTEGRATION OF TEXT PROCEDURES AND ECOPRINT IN THE CONTEXT OF ART: ITS IMPACT ON STUDENTS MOOD AT SMP NEGERI 6 BANDA ACEH - Cut Mawar Helmanda; Meutia Zahara; Siti Salsabila (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
This community service carried out by lecturers from the Faculty of Islamic Studies at University of Muhammadiyah Aceh (UNMUHA) at SMP Negeri 6 Banda Aceh aims to provide practical experience in the art of ecoprint, integrated with the use of English as the instructional language for procedural texts. The goal is to equip students with knowledge related to ecoprint and an understanding of using English to convey the steps in creating ecoprints. This approach is intended to create enjoyable learning, stimulate students’ moods positively, and encourage high creativity. In this program, students are guided to perform the ecoprint process using English as the instructional language and in the production process. Through this process, it is hoped that students not only understand the practical process of ecoprint but also improve their ability to use English. Additionally, this activity is expected to provide a positive experience for students, increase their interest in learning, and improve their mood. The community service activity conducted at SMP Negeri 6 by class IX-6 has had a positive impact on the students’ moods, especially through the application of procedural texts in English to create ecoprints. The integration of procedural texts and ecoprint techniques in the context of art has positively influenced the mood of students at SMP Negeri 6 Banda Aceh. The students showed high interest in textile art using the ecoprint technique, which was reflected in their active participation. Keywords: ecoprint, text procedures, art.